PENERAPAN MODEL PEMBELAJARAN INFORMATION SEARCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KELAS X SMA NEGERI 5 BONE - Hasisa Haruna (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This research is a Classroom Action Research (CAR) which aims to determine the improvement of learning outcomes in Economics through the Information Search Learning Model in class X SMA Negeri 5 Bone. The subjects of this study were 30 students in the odd semester of the 2020/2021 academic year. This implementation was carried out for four meetings through two cycles consisting of four activities, namely: planning, implementation, observation, and reflection. The data collection model was carried out by means of observation and tests. While the data collected were analyzed using descriptive analysis. Based on the data, the results showed that the learning outcomes in the first cycle with an average of 66.25 and in the second cycle increased to 82.5 and the increase in student mastery in the first cycle was 25% and in the second cycle was 90%. From the results of the study, it can be concluded that the Information Search Learning Model can improve social studies learning outcomes in class X SMA Negeri 5 Bone.